Steady‐state and transient hydrothermal analyses of single‐phase natural circulation loop using water‐based tri‐hybrid nanofluids. Issue 6 (28th January 2021) - Sahu, Mayaram; Sarkar, Jahar; Chandra, Laltu
Abstract: Transient and steady‐state characteristics of the natural circulation loop are studied using various water‐based tri‐hybrid (different nature and shaped nanoparticles) nanofluids. Effects of input power, loop inclination and loop aspect ratio on the mass flow rate, effectiveness, and entropy generation rate are studied. Results disclose that tri‐hybrid nanofluids reduce the oscillation and attain steady state faster than water. Effectiveness increases and entropy generation rate decreases by using tri‐hybrid nanofluids. Nanoparticle shape has found a significant impact. Al2 O3 + Cu + CNT/water shows the best performance. The mass flow rate increases with input power, loop aspect ratio, whereas, reduces with loop inclination. Effectiveness decreases and then increases with input power, whereas increases with loop inclination and decreases with loop aspect ratio. Entropy generation upsurges with input power and loop inclination, whereas decreases with loop aspect ratio. Loop aspect ratio of 1.5 to 3 is found suitable for better performance.